CRC Dictionary of Agricultural Sciences. - Helen F. Smith (Issues in Science and Technology Librarianship)
The article reviews the book CRC Dictionary of Agricultural Sciences. Boca Raton, Fla.: CRC Press, 2002 by Robert A. Lewis.